Pattern-recognition receptors in endometriosis: A narrative review - Guo, Bao; Chen, Jia hua; Zhang, Jun hui; Fang, Yuan; Liu, Xiao jing; Zhang, Jing; Zhu, Hai qing; Zhan, Lei (Frontiers in Immunology, 2023)
Endometriosis is closely associated with ectopic focal inflammation and immunosuppressive microenvironment. Multiple types of pattern recognition receptors (PRRs) are present in the innate immune system, which are able to detect pathogen-associated molecular patterns (PAMPs) and danger-associated molecular patterns (DAMPs) in both intracellular and external environments. However, the exact role of PRRs in endometriosis and the underlying molecular mechanism are unclear. PRRs are necessary for the innate immune system to identify and destroy invasive foreign infectious agents. Mammals mainly have two types of microbial recognition systems. The first one consists of the membrane-bound receptors, such as toll-like receptors (TLRs), which recognize extracellular microorganisms and activate intracellular signals to stimulate immune responses. The second one consists of the intracellular PRRs, including nod-like receptors (NLRs) and antiviral proteins retinoic acid-inducible gene I (RIG-I) and melanoma differentiation-associated gene 5 (MDA-5) with helix enzyme domain. In this review, we mainly focus on the key role of PRRs in the pathological processes associated with endometriosis. PRRs recognize PAMPs and can distinguish pathogenic microorganisms from self, triggering receptor ligand reaction followed by the stimulation of host immune response. Activated immune response promotes the transmission of microbial infection signals to the cells. As endometriosis is characterized by dysregulated inflammation and immune response, PRRs may potentially be involved in the activation of endometriosis-associated inflammation and immune disorders. Toll-like receptor 2 (TLR2), toll-like receptor 3 (TLR3), toll-like receptor 4 (TLR4), nod-like receptor family caspase activation and recruitment domain (CARD) domain containing 5 (NLRC5), nod-like receptor family pyrin domain containing 3 (NLRP3), and c-type lectin receptors (CLRs) play essential roles in endometriosis development by regulating immune and inflammatory responses. Absent in melanoma 2 (AIM2)-like receptors (ALRs) and retinoic acid-inducible gene I-like receptors (RLRs) may be involved in the activation of endometriosis-associated immune and inflammation disorders. PRRs, especially TLRs, may serve as potential therapeutic targets for alleviating pain in endometriosis patients. PRRs and their ligands interact with the innate immune system to enhance inflammation in the stromal cells during endometriosis. Thus, targeting PRRs and their new synthetic ligands may provide new therapeutic options for treating endometriosis.